Incidental Detection of Papillary Renal Cell Carcinoma in Nephrectomy Specimen for Chronic Pyelonephritis - Sana Ahuja; Adil Aziz Khan; Sufian Zaheer (Annals of Urologic Oncology, 2024)
Papillary renal cell carcinoma (PRCC), though often asymptomatic in its early stages, presents unique diagnostic challenges. This case report describes the serendipitous discovery of a 1cm PRCC nodule initially missed on radiological investigations. Through meticulous pathological evaluation, PRCC was identified, underscoring the crucial interplay between urological and pathological perspectives. Therapeutic decisions, guided by tumor characteristics and clinical considerations, highlighted the necessity for comprehensive multidisciplinary collaboration. This case emphasizes the importance of thorough evaluation and interdisciplinary cooperation in optimizing diagnostic accuracy and therapeutic strategies in renal pathology.